Frozen section library head and neck - Zhai, Qihui "Jim." (Frozen Section Library., 2011)
Intraoperative frozen section interpretation is the base for treatment for the patient within the operating room. It requires immediate answer for the surgeon's specific question and the subsequent consequences are frequently irreversible. The pathologist should be very familiar with the related differential diagnosis of the involved organ. Additionally, the pathologist needs to know many pitfalls and freezing artifacts in each organ and the clinical implications each diagnosis may result in. "Frozen Section Library: Head and Neck" will provide a convenient, user-friendly handbook to.